HUBUNGAN TINGKAT STRES DALAM PENGERJAAN SKRIPSI DENGAN KEJADIAN INSOMNIA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS LAMBUNG MANGKURAT - Fauzan, Muhammad Andy; Khairiah, Siti; Istiana, Istiana (Universitas Lambung Mangkurat, 2024)
Abstract: Stress is a condition of excessive pressure that cannot be overcome as a non-specific body response, so that it can affect physical, psychological and social health. Insomnia is a condition of difficulty in the sleep process which is associated with disturbances in the quantity, quality, and time of sleep in an individual. This study aims to analyze the relationship between stress levels in writing a thesis and the incidence of insomnia in students at the Faculty of Medicine, Lambung Mangkurat University. This research is an analytical observational study with a cross sectional approach. Sampling used simple random sampling in November 2023. Data collection used the PSS questionnaire and ISI questionnaire. Data analysis used the Spearman Rank test. The results showed that 25 respondents or 37.3% experienced mild stress, 37 respondents or 55.2% experienced moderate stress, 5 respondents or 7.4% experienced severe stress. 24 respondents or 35.8% had normal or no insomnia, 34 respondents or 50.7% experienced mild insomnia, 9 respondents or 13.4% experienced moderate insomnia, and no respondents experienced severe insomnia. There is a significant relationship between the level of stress and the incidence of insomnia in final year Undergraduate Medical Study Program students working on their thesis with a positive value indicating a sufficient and unidirectional relationship. Keywords: Stress level, insomnia, thesis Abstrak: Stres merupakan kondisi adanya tekanan berlebih yang tidak mampu diatasi sebagai suatu respon tubuh yang tidak spesifik, sehingga dapat mempengaruhi kesehatan fisik, psikologi, dan sosial. Insomnia merupakan kondisi kesulitan dalam proses tidur yang dihubungkan dengan adanya gangguan kuantitas, kualitas, dan waktu tidur pada seorang individu. Penelitian ini bertujuan untuk menganalisis hubungan tingkat stres dalam pengerjaan skripsi dengan kejadian insomnia pada mahasiswa Fakultas Kedokteran Universitas Lambung Mangkurat. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Pengambilan sampel menggunakan simple random sampling pada bulan November 2023. Pengumpulan data menggunakan kuesioner PSS dan kuesioner ISI. Analisis data menggunakan uji Spearman Rank. Hasil penelitian menunjukkan bahwa 25 responden atau 37,3% mengalami stres ringan, 37 responden atau 55,2% mengalami stres sedang, 5 responden atau 7,4% mengalami stres berat. 24 responden atau 35,8% normal atau tidak insomnia, 34 responden atau 50,7% mengalami insomnia ringan, 9 responden atau 13,4% mengalami insomnia sedang, dan tidak ada responden yang mengalami insomnia berat. Terdapat hubungan yang signifikan antara tingkat stres dengan kejadian insomnia pada mahasiswa Program Studi Kedokteran Program Sarjana tingkat akhir dalam pengerjaan skripsi demgan nilai positif menunjukkan hubungan yang cukup dan searah. Kata-Kata Kunci: Tingkat stres, insomnia, skripsi